Diagnósticos de enfermagem em pacientes no pós-operatório imediato de prostatectomia de um Hospital Universitário de Natal-RN - Saldanha, Elisandra de Araújo (2011)
The characterization of the nursing diagnoses in prostatectomized patients is important to provide an unique nursing language, facilitating the communication between professionals and patients. The objective of this study was to analyze the nursing diagnoses of patients in the immediate prostatectomy postoperative period. This is a cross-sectional and descriptive study, developed at the surgical-clinic of Onofre Lopes University Hospital, in the Natal City RN - Brazil. The sample was composed of 50 patients included by the criteria: have presented a diagnosis of a benign prostatic hyperplasia or a prostate cancer, have been subjected to a prostate surgery at the mentioned hospital, and have been in the immediate postoperative period at the moment of the data collection. The exclusion criteria were: haven t been in an appropriate physical and mental condition, have presented a brain vascular disease, a lung disease, an advanced liver disease, a heart disease or a extensive coronary artery disease. The data collection instruments were: the script of an interview and physical examination. The data collection period was between November 2010 and April 2011. The data were organized in two phases: the diagnostic process and the construction of the database. The project was approved by the Ethics Committee of the Federal University of Rio Grande do Norte The results showed that most patients came from the countryside, was living with partners, had an average of 67.78 years, was pensionerthose with low schooling, Catholic and often did not perform preventive examinations of prostatic disease. The patients showed an average of 9.48 nursing diagnoses, defining characteristics 21.70 and 20.72 related or risk factors per patient. We identified 30 nursing diagnoses, of which 7 were above the 75 percentile: Risk of falls, Impaired ambulation, Risk of infection, Self-care deficit bath / hygiene and dress up and Risk for deficient fluid volume. The top six nursing diagnoses were in all patients, and therefore could not apply any statistical test. The others ND were associated with their defining characteristics and related or risk factors. We conclude that the nursing diagnoses identified in this study contribute to the progress of the nursing care to the prostatectomized patients in post-surgery period, allowing the deployment of nursing actions for the effective resolution of identified problems